Pengaruh Fasilitas Dan Promosi Terhadap Minat Berkunjung : Survei Pada Pengunjung Kolam Renang ASB Rajapolah Kabupaten Tasikmalaya - Adnan Robi Senjaya; Ari Arisman; Depy Muhamad Pauzy (Journal of Islamic Economics and Finance, 2023)
This study aims to determine the effect of facilities and promotions simultaneously on the interest in visiting the ASB Rajapolah Swimming Pool. Partial influence of facilities and promotions on interest in visiting the ASB Rajapolah Swimming Pool. The method used in this research is quantitative with a survey approach. With a research sample of 100 people as ASB Rajapolah Swimming Pool respondents based on 100 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. The test results show that facilities and promotions simultaneously have a significant effect on visiting. Partially, the facility variable has a significant effect on the intention to visit, as well as the promotion variable, which partially has a significant effect on the intention to visit.